Molecular and morphological characterization of introgression lines with resistance to bacterial leaf blight and blast in rice - Varanasi, Yasaswini Vishnu Priya; Isetty, Subhakara Rao; Revadi, Padmashree; Balakrishnan, Divya; Hajira, Shaik; Prasad, Madamsetty Srinivasa; Laha, Gouri Shankar; Perraju, Puvvada; Singh, Uma Maheshwar; Singh, Vikas Kumar; Kumar, Arvind; Sundaram, Raman Meenakshi; et al. (MDPI, 2023)
The present study evaluates marker assisted forward breeding (MAFB)-derived disease resistant introgression lines (ILs) which do not have the targeted resistance genes for bacterial blight (xa5 + xa13 + Xa21) and blast (Pi2 + Pi9 + Pi54). The ILs were derived in the background of two elite rice cultivars, Krishna Hamsa [Recurrent Parent 1 (RP1)] and WGL 14 (RP2), involving multi-parent inter-crossing. Molecular characterization with gene specific markers for seven reported resistance genes each for bacterial blight (Xa33, Xa38, xa23, Xa4, xa8, Xa27 and Xa41) and blast (Pi1, Pi20, Pi38, Pib, Pitp, Pizt and Pi40) revealed the presence of xa8 and Xa38, in addition to the targeted xa5, xa13 and Xa21 for bacterial blight resistance and Pi1, Pi38, Pi40, Pi20, Pib and Pipt, in addition to the targeted Pi9 and Pi54, for blast resistance in various combinations. A maximum of nine resistance genes xa5 + Xa21 + Pi54 + xa8 + Pipt + Pi38 + Pi1 + Pi20 + Pib was observed in RP1-IL 19030 followed by eight genes xa5 + xa13 + Xa21 + xa8 + Pi9 + Pipt + Pi1 + Pi20 in two RP2-ILs, 19344 and 19347. ANOVA revealed the presence of significant variability for all the yield traits except “days to 50% flowering” (DFF). Box plots depicted the seasonal differences in the phenotypic expression of the yield traits. There was significant positive association of grain yield with days to flowering, tiller number and panicle number. Thousand grain weight is also significantly and positively correlated with grain yield. On the contrary, grain yield showed a significantly negative association with plant height. Multi-parent selective inter-crossing in the present study not only led to the development of high yielding disease resistant ILs but also enhanced recovery of the recurrent parent via selection for essential morphological features. More than 90.0% genetic similarity in the ILs based on SNP-based background selection demonstrated the success of multi-parent selective intercrossing in the development of disease resistant NILs.